2013
DOI: 10.17221/122/2012-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

The effect of real exchange rates and their volatilities on the selected agricultural commodity exports: A case study on Turkey, 1971-2010

Abstract: 235After the collapse of the Brettonwood system in 1973, most of the countries have abandoned to use solely the fixed exchange rate regime, and different countries have adapted different exchange rate regimes. Then, the impact of both the exchange rate level and the exchange rate volatility or variability especially on exports, the bilateral trade flows and the volumes of trade have been empirically and theoretically discussed.A large number of studies examine both the effect of the exchange rate and its volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Conversely, the depreciation of Turkish Lira negatively affects the exports three commodities in our sample, namely tobacco, hazelnut (in the case of exports to Europe, which constitute 76% of total hazelnut exports) and grape-raisin, which have important shares in the Turkish agricultural exports. Although the negative relationship between exchange rates and exports of hazelnut, grape-raisin and tobacco can be attributable to the monopoly power of Turkish producers in these commodities as stated in Yanikkaya et al (2013), their consistent insensitivity to the domestic supports or border measures is interesting since hazelnut and tobacco are highly subject to government interventions. On the effects of exchange rate volatility, our analysis show that although there are mixed results, general effect of volatilities on the Turkish agricultural exports is negative.…”
Section: VII Regression Results For Developed and Developing Countrmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the depreciation of Turkish Lira negatively affects the exports three commodities in our sample, namely tobacco, hazelnut (in the case of exports to Europe, which constitute 76% of total hazelnut exports) and grape-raisin, which have important shares in the Turkish agricultural exports. Although the negative relationship between exchange rates and exports of hazelnut, grape-raisin and tobacco can be attributable to the monopoly power of Turkish producers in these commodities as stated in Yanikkaya et al (2013), their consistent insensitivity to the domestic supports or border measures is interesting since hazelnut and tobacco are highly subject to government interventions. On the effects of exchange rate volatility, our analysis show that although there are mixed results, general effect of volatilities on the Turkish agricultural exports is negative.…”
Section: VII Regression Results For Developed and Developing Countrmentioning
confidence: 99%
“…In another commodity-specific study based on the data for dried 13 Impacts of Agricultural Supports on Exports of Individual Agricultural Products in Turkey figs, grapes and tobacco, Buguk et al (2003) find that there is no significant relationship between exchange rate or its volatility and the exports of aforesaid commodities in the case of Turkey. Yanikkaya et al (2013) examine the effect of real exchange rate and its volatility on agricultural export flows of Turkey at the commodity level. They argue that although the real exchange rate has an important effect on Turkish agricultural commodity exports, exchange rate volatility hasn't.…”
Section: Iiii Agricultural Subsidies/distortions and Agricultural Tmentioning
confidence: 99%
See 1 more Smart Citation
“…With a series of exchange rate reforms, the yuan's misalignment issue has diminished in recent years, which is expected to have far‐reaching implications on exports. On the one hand, many studies have noted the negative export impact resulting from real exchange rate appreciation (Baek & Koo, 2011; Berman et al., 2012; Cushman, 1983; Lamb, 2000; Li et al., 2015; Yanikkaya et al., 2013). On the other hand, however, aggravated market competition, restructured product mixes, and ameliorated vertical integration might lead to quality improvements that enhance firms’ capability to cope with the challenge of losing price competitiveness, which would increase exports in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current literature on the relationship between exchange rate and agricultural trade has been concerned with the trade volume. They consistently concluded that both currency appreciations and an increased exchange rate volatility could result in reduced agricultural exports (Baek & Koo, 2011; Lamb, 2000; Yanikkaya et al., 2013). Specifically, they found the agricultural export volume to decline by 0.05–1.98% on average with a 1% appreciation of the exporter currency.…”
Section: Introductionmentioning
confidence: 99%